2018
DOI: 10.1530/jme-18-0016
|View full text |Cite
|
Sign up to set email alerts
|

40 YEARS OF IGF1: Role of IGF-binding proteins in regulating IGF responses to changes in metabolism

Abstract: The IGF-binding protein family contains six members that share significant structural homology. Their principal function is to regulate the actions of IGF1 and IGF2. These proteins are present in plasma and extracellular fluids and regulate access of both IGF1 and II to the type I IGF receptor. Additionally, they have functions that are independent of their ability to bind IGFs. Each protein is regulated independently of IGF1 and IGF2, and this provides an important mechanism by which other hormones and physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 277 publications
(262 reference statements)
2
88
0
1
Order By: Relevance
“…M6PR expressed in peripheral tissues (Duffy et al, 1988). The transport of IGF1 or IGF2 into brain via the BBB IGFR may be inhibited, because IGF1 and IGF1 are avidly bound, >99%, in plasma by a family of IGF binding proteins (IGFBP; Clemmons, 2018). It is likely that IGFBP complex formation with either IGF1 or IGF2 blocks BBB transport of the peptide, because an IGF2-lysosomal enzyme fusion protein does not cross the BBB following IV administration (Kan et al, 2014).…”
Section: Bbb Receptor-mediated Transportersmentioning
confidence: 99%
“…M6PR expressed in peripheral tissues (Duffy et al, 1988). The transport of IGF1 or IGF2 into brain via the BBB IGFR may be inhibited, because IGF1 and IGF1 are avidly bound, >99%, in plasma by a family of IGF binding proteins (IGFBP; Clemmons, 2018). It is likely that IGFBP complex formation with either IGF1 or IGF2 blocks BBB transport of the peptide, because an IGF2-lysosomal enzyme fusion protein does not cross the BBB following IV administration (Kan et al, 2014).…”
Section: Bbb Receptor-mediated Transportersmentioning
confidence: 99%
“…IGFBP5/Igfbp5a has been shown to inhibit and/or potentiate IGF actions in mammalian and zebrafish cells (Zheng et al, 1998;Ren et al, 2008;Dai et al, 2010;Liu et al, 2018). How the same protein exerts these opposing biological effects is not completely understood, but the importance of IGFBP5 proteinases has been suggested (Zheng et al, 1998;Oxvig, 2015;Clemmons, 2018;Allard and Duan, 2018). Using an optimized in situ hybridization protocol and qPCR analysis of FACS-isolated NaR cells, we found that Papp-aa is highly expressed in NaR receptor-mediated Akt-Tor activity in NaR cells is off.…”
Section: Discussionmentioning
confidence: 92%
“…IGFBPs are a family of secreted proteins that bind IGF ligands with high affinity and regulates their availability to the IGF1 receptor (Baxter, 2014;Clemmons, 2018;Allard and Duan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating IGFBP-1, which is produced mainly by the liver, is normally suppressed in postprandial state by hyperinsulinemia [78] and increased glycolysis [79]. As the levels of IGFBP-1 fluctuate throughout the day in response to feeding and fasting, it acutely regulates the availability of free IGF-1, which has insulin-sensitizing effects [80]. In adipose tissue, IGFBP-1 inhibits IGF-1 stimulated proliferation of preadipocytes [81], resulting in reduced fat mass [82].…”
Section: Discussionmentioning
confidence: 99%